The impact of electricity consumption on economic growth in Malaysia: evidence from ARDL bounds testing - Ahmad Kamal, Muhammad Khalid; Mazlan, Nur Syazwani (Penerbit UKM, Universiti Kebangsaan Malaysia, 2018)
This paper investigates the relationship between electricity consumption and economic growth in Malaysia during the period 1971-2014. The results from the ARDL bounds testing approach, as developed by Pesaran et al. (2001), showed that there was a cointegration between electricity consumption and real Gross Domestic Product (GDP). There was also a stable long-run relationship between other determinants such as foreign direct investment (FDI) and real GDP. Moreover, we found that electricity consumption, FDI, and real capital positively affected economic growth in the short-run. Therefore, it is recommended that policies should be geared towards improving current energy production and encouraging the exploration of alternative energy sources in order to promote growth in the Malaysian economy.